Eunuch and emperor in the great age of Qing rule - Kutcher, Norman Alan (University of California Press, 2018)
"This book offers a new understanding of eunuchs and their connection to imperial rule in early-to- mid-Qing China (1644-1800). Historians have traditionally viewed this period as one in which China's greatest emperors crafted policies that curtailed eunuch power, following its surge in the Ming dynasty (1368-1644). Using archival, epigraphic, and other newly available sources, Norman Kutcher demonstrates the continuing influence and even empowerment of eunuchs throughout this period. The book traces this empowerment to eunuchs' exploitation of the gap between imperial rhetoric and practice and to their networking and other collective action in and beyond the city of Beijing"...Provided by publisher